2019
DOI: 10.24251/hicss.2019.539
|View full text |Cite
|
Sign up to set email alerts
|

Externalities in Charitable Crowdfunding

Abstract: This study examines how the existence of multiple charitable campaigns supporting similar causes on the same platform influence the donations received by each campaign. The existence of multiple campaigns supporting similar causes can have negative externalities as they compete for donors. However, the existence of additional campaigns can also result in positive externalities as potential donors benefit from a larger variety of projects to choose from. This study observes negative and positive externalities f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…First, both funding goal and funding duration have a U-shaped relationship with crowdfunding performance, suggesting that donors rely on funding information signals to make funding-related decisions. Contrary to previous studies that identify a positive or negative linear relationship between funding goal/duration and crowdfunding performance in the general crowdfunding context (Bukhari et al, 2020;Lee and Park, 2019;Sulaeman and Lin, 2018), our empirical findings indicate a nonlinear relationship in the medical crowdfunding context.…”
Section: Robustness Checkscontrasting
confidence: 99%
See 1 more Smart Citation
“…First, both funding goal and funding duration have a U-shaped relationship with crowdfunding performance, suggesting that donors rely on funding information signals to make funding-related decisions. Contrary to previous studies that identify a positive or negative linear relationship between funding goal/duration and crowdfunding performance in the general crowdfunding context (Bukhari et al, 2020;Lee and Park, 2019;Sulaeman and Lin, 2018), our empirical findings indicate a nonlinear relationship in the medical crowdfunding context.…”
Section: Robustness Checkscontrasting
confidence: 99%
“…Although previous studies identify the significant effects of funding goal and funding duration on crowdfunding performance, the findings are inconsistent. In the context of general crowdfunding, some studies have found that funding goal and funding duration have negative effects on the success of funding (Bukhari et al, 2020), whereas other studies have reported that funding goal (Sulaeman and Lin, 2018) and funding duration (Lee and Park, 2019) have positive effects on funding success. Our study provides a possible explanation for the mixed findings by proposing nonlinear effects of funding goal and duration on crowdfunding performance and providing empirical evidence that funding goal and duration have U-shaped relationships with medical crowdfunding performance.…”
Section: Theoretical Contributionsmentioning
confidence: 99%
“…Particularly popular or successful campaigns are difficult to anonymise entirely due to media coverage and spread; in these cases, we only share details pertinent to the research. Previous research has found that campaigns with stronger writing and fewer grammatical errors receive more donations (Sulaeman & Lin, 2018). Consequently, in reporting direct quotes from campaign pages, we have retained, as much as possible, the syntax, punctuation and even grammatical and spelling errors of the original text.…”
Section: Methodsmentioning
confidence: 99%
“…Drawing from a large dataset of Kickstarter projects, the existence of spelling errors can also decrease the chances of success by 13% [ 23 ]. Sulaeman and Lin [ 51 ] showed that fewer spelling errors on charitable fundraising campaigns lead to more donors contributing and a higher total amount of donations. According to GoFundMe [ 47 ], since most of the crowd uses online searches for keywords to find a cause to support, spelling is a critical element for Google’s algorithm screening process to precisely detect your campaign to give the most relevant answers to the people query.…”
Section: Literature Reviewmentioning
confidence: 99%